MEMBAHAS PERAN MANAJEMEN STRATEGIS DALAM PERENCANAAN PENDIDIKAN ISLAM - Syifa Hanifah Syandra; Nadia Putri Kamila; Romlah Romlah; Abdurrahman Abdurrahman (Jurnal Manajemen Pendidikan, 2025)
This study discusses the role of strategic management in strengthening the effectiveness and competitiveness of Islamic educational institutions amid globalization and technological disruption. Using a systematic literature review approach, this research examines various national and international studies from 2019–2025 to analyze the stages of strategy formulation, implementation, and evaluation applied within the context of Islamic education. The findings reveal that strategic management functions not only as an administrative tool but also as a value-based framework guiding institutional policies to align with the principles of tawhid, justice, and maslahah (public benefit). Internal and external environmental analyses enable institutions to identify opportunities and challenges, while implementation emphasizes visionary leadership, participatory culture, and the wise use of technology. However, the study also highlights several constraints, such as limited managerial literacy, inadequate resources, and the tendency toward formalistic planning practices. Therefore, value-based and sustainability-oriented strategic management is essential for Islamic educational institutions to adapt, innovate, and maintain their relevance in the face of global transformation.